The Remission Phase in Type 1 Diabetes: Role of Hyperglycemia Rectification in Immune Modulation - Tang, Rong; Zhong, Ting; Wu, Chao; Zhou, Zhiguang; Li, Xia (Frontiers in Endocrinology, 2019)
The remission phase (or honeymoon period) is a spontaneous "temporary cure stage" in type 1 diabetes course, which provides a good human model for studying β cell protection. The exact mechanisms are still uncertain but one of the generally recognized mechanisms is that correction of "glucotoxicity" by exogenous insulin therapy leads to "β cell rest" and β cell recovery. Beyond this, the remission phase is accompanied by changes in various immune cells and immune molecules, indicating down-regulation of immune response and induction of immune tolerance. The role of hyperglycemia rectification in the regulation of immune response should be emphasized because glucose metabolism is critical to maintain the normal function of immune system. Here, recent evidence of immune modulation based on the rectification of hyperglycemia from multiple aspects such as immune cells, inflammatory cytokines, biomolecules and cell antigenicity was reviewed. It should be noteworthy that the interaction between glucose metabolism and immune plays an important role in the pathogenesis of the remission phase. The best intervention strategy may be the combination of strict glycemic control and immune modulation to protect β cell function as early as possible.